Daily returns seasonality and impact of stock index futures: evidence from the Kuala Lumpur Stock Exchange - Mohamad, Azhar; Bacha, Obiyathulla Ismath; Ibrahim, Mansor (2003)
This paper examines the impact of Stock Index Futures (SIF) trading on Day of Week (DOW) pattern of daily KLSE returns. We address a total of four research questions using both a simple OLS model and a GARCH(1,1) specification. Three daily return measures, CTC , OTC and CTO are used. The impact on DOW pattern of the new T+3 day settlement is also examined.